2016
DOI: 10.9734/jsrr/2016/23095
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Child Malnutrition in the Tamale Teaching Hospital, Ghana

Abstract: Introduction: Malnutrition is an essential global public health challenge affecting millions of people. The burden of malnutrition is huge especially among children in developing countries and poverty stricken regions. Aims: This study investigated the distributions, co-morbidities, and admission outcomes among malnourished children in the paediatric ward of the Tamale Teaching Hospital, Ghana. Study Design: A retrospective health facility based study was employed. Place and Duration of Study: The study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…The distribution showed that 161 of the children had diarrhea (43.9%), 122 (33.2%) had respiratory tract infections, and 143 (39.0%) had malaria as the top three associated comorbidities with children under 5 years admitted at Magumeri General Hospital during the study period, this is consistent with the body of evidence that shows that the most significant comorbidities reported in children with SAM are infectious disease i.e. diarrhea, pneumonia, acute respiratory tract infections as well as malaria and measles [16,17,19,20]. Concerning admission and treatment outcomes, many of the cases were managed successfully, with 79.6 % reported to have fully recovered and discharged from the hospital, 8.7% of the cases were referred, 7.1% defaulted and 17 (4.1%) died, this is similar to a study in Ethiopia [16].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The distribution showed that 161 of the children had diarrhea (43.9%), 122 (33.2%) had respiratory tract infections, and 143 (39.0%) had malaria as the top three associated comorbidities with children under 5 years admitted at Magumeri General Hospital during the study period, this is consistent with the body of evidence that shows that the most significant comorbidities reported in children with SAM are infectious disease i.e. diarrhea, pneumonia, acute respiratory tract infections as well as malaria and measles [16,17,19,20]. Concerning admission and treatment outcomes, many of the cases were managed successfully, with 79.6 % reported to have fully recovered and discharged from the hospital, 8.7% of the cases were referred, 7.1% defaulted and 17 (4.1%) died, this is similar to a study in Ethiopia [16].…”
Section: Discussionsupporting
confidence: 78%
“…217 of the cases were male (59.1%) while 150 were female (40.9%) which is like a study conducted in Ayder Referral Hospital, Tigray Ethiopia by [17], in 2015 and in Tamale Teaching Hospital Ghana [20].…”
Section: Discussionsupporting
confidence: 52%